'Memory must be defended': Beyond the politics of mnemonical security. (June 2015) - Mälksoo, Maria
This article supplements and extends the ontological security theory in International Relations (IR) by conceptualizing the notion of mnemonical security. It engages critically the securitization of memory as a means of making certain historical remembrances secure by delegitimizing or outright criminalizing others. The securitization of historical memory by means of law tends to reproduce a sense of insecurity among the contesters of the 'memory' in question. To move beyond the politics of mnemonical security, two lines of action are outlined: (i) the 'desecuritization' of social remembrance in order to allow for its repoliticization, and (ii) the rethinking of the self–other relations in mnemonic conflicts. A radically democratic, agonistic politics of memory is called for that would avoid the knee-jerk reactive treatment of identity, memory and history as problems of security. Rather than trying to secure the unsecurable, a genuinely agonistic mnemonic pluralism would enable different interpretations of the past to be questioned, in place of pre-defining national or regional positions on legitimate remembrance in ontological security terms.